Peripheral Nerve : Health and Medicine in Cold War Latin America - Necochea López, Raúl; Birn, Anne-Emanuelle, 1964- (American encounters/global interactions., 2020)
"PERIPHERAL NERVE is an edited volume that brings together scholars from the United States, Canada, and Latin America to challenge the dominant narrative that the United States was the primary medical interlocutor in Latin America during the Cold War. It chronicles the experiences of Latin Americans who sought alternative channels of health and medical solidarity with the Soviet Union and via South-South solidarities within and beyond Latin America. These channels, which included anti-colonial psychoanalysis in Argentina and the emergence of local and specialized fertility research in Puerto Rico, were alternative to mainland U.S. interests and served as a vital part of health policy and medical developments in the Global South. Ultimately, the collection highlights the multivalent nature of the Latin American Cold War as a significant perspective for studies of medicine and public health, international development, and international relations. The volume is divided into three parts, with three or four chapters each, that explore leftist affinities and U.S. suspicions, expertise and contested ideologies, and health politics and publics. Part I includes a chapter by Katherine E. Bliss where she showcases the life and contributions of Lini de Vries, a community health worker who developed health education programs for Indigenous communities in Oaxaca, but who came to be viewed as a threat to national U.S. interests because of her communist ties. Chapter 2 by Nicole L. Pacino examines how the Rockefeller Foundation refused to fund medical schools in Bolivia because of the revolutionary consciousness and communist values of the country and its students. Part II contains a chapter by Raúl Necochea López, co-editor of the volume, who uncovers the asymmetrical dynamics that emerged in Puerto Rico when the United States attempted to implement the mass utilization of birth control technologies out of fear that an increasing population size would promote a greater sympathy for communism. Lastly, Part III incorporates a chapter by Cheasty Anderson delving into how Sandinista Nicaragua achieved full-coverage health care for its population vis-à-vis Cuba, a relationship outside the nexus of the Soviet-U.S. rivalry. This volume will be of interest to scholars and students in Latin American studies, medicine and public health studies, communist studies, and studies of the Cold War"--